2017
DOI: 10.1002/pmic.201700186
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Ancylostoma Caninum Secretome Provides New Information on Hookworm–Host Interactions

Abstract: Hookworm infection is a major tropical parasitic disease affecting almost 500 million people worldwide. These soil-transmitted helminths can survive for many years in the intestine of the host, where they feed on blood, causing iron deficiency anemia and other complications. These parasites release a variety of molecules known as excretory/secretory products (ESPs) that are involved in many different biological processes that govern parasite survival. Using a combination of separation techniques such as SDS-PA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…However, it was not until 2020 that the first comprehensive proteomic analysis of a secretome of a human hookworm was reported [ 34 ]. In this study of Necator americanus [ 34 ], a total of 198 ES proteins were identified in the adult stage, 90% of which had homologs in the secretomes of three other strongylid nematodes (i.e., Ancylostoma caninum , Heligmosomoides polygyrus/bakeri and Nippostrongyus brasiliensis ) [ 31 , 35 , 36 ], confirming the value of these reference species for such studies. Of the 198 ES proteins identified/characterised for adult Necator americanus , ~ 30% of them belong to the group of SCP/TAPS proteins with one or two ‘SCP’ domains [ 34 ].…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodessupporting
confidence: 54%
See 1 more Smart Citation
“…However, it was not until 2020 that the first comprehensive proteomic analysis of a secretome of a human hookworm was reported [ 34 ]. In this study of Necator americanus [ 34 ], a total of 198 ES proteins were identified in the adult stage, 90% of which had homologs in the secretomes of three other strongylid nematodes (i.e., Ancylostoma caninum , Heligmosomoides polygyrus/bakeri and Nippostrongyus brasiliensis ) [ 31 , 35 , 36 ], confirming the value of these reference species for such studies. Of the 198 ES proteins identified/characterised for adult Necator americanus , ~ 30% of them belong to the group of SCP/TAPS proteins with one or two ‘SCP’ domains [ 34 ].…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodessupporting
confidence: 54%
“…A particular example is the recent study of the dog hookworm Ancylostoma caninum . Using advanced LC-MS/MS combined with in-gel and off-gel electrophoresis, in 2017, Morante et al [ 31 ] identified nearly three times ( n = 315) the number of proteins reported previously ( n = 105) by Muvenna et al [ 32 ] in 2009. Facilitated by state-of-the-art MS and underpinned by genomic information, a re-analysis of the proteome only required a quarter of previously required amount of ES products (equating to 150 μg of protein versus 660 μg previously) [ 32 ].…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodesmentioning
confidence: 99%
“…This family of proteins is abundantly expressed by parasitic nematodes and trematodes. For instance, they represent 35% of the ES products of the hookworm Ancylostoma caninum [67] and have been found in free-living and plant nematodes (reviewed by [68]). Their role is still unknown, although they have been suggested to play roles in fundamental biological processes such as larval penetration [69] and modulation of the immune response [70,71], in the transition from the free-living to the parasitic stage [72], and have even been explored as vaccine candidates against hookworm infections [73].…”
Section: Discussionmentioning
confidence: 99%
“…This family of proteins is abundantly expressed by parasitic nematodes and trematodes. For instance, they represent 35% of the ES products of the hookworm Ancylostoma caninum [67], and have been found in free-living and plant nematodes (reviewed by [68]). Their role is still unknown, although they have been suggested to play roles in fundamental biological processes such as larval penetration [69], modulation of the immune response [70, 71], in the transition from the free-living to the parasitic stage [72] and have even been explored as vaccine candidates against hookworm infections [73].…”
Section: Discussionmentioning
confidence: 99%